Using occupancy-based camera-trap surveys to assess the Critically Endangered primate Macaca nigra across its range in North Sulawesi, Indonesia. Issue 6 (29th November 2020) - Johnson, Caspian L.; Hilser, Harry; Linkie, Matthew; Rahasia, Rivo; Rovero, Francesco; Pusparini, Wulan; Hunowu, Iwan; Patandung, Alfons; Andayani, Noviar; Tasirin, John; Nistyantara, Lukita A.; Bowkett, Andrew E.
Abstract: Primates are one of the most threatened groups of mammals. Understanding their patterns of population occurrence and abundance, especially in response to threats, is critical for informing conservation action. The crested black macaque Macaca nigra is the only Critically Endangered species of Sulawesi's seven endemic macaques. Little is known about its distribution or its response to deforestation and hunting. We conducted a camera-trap survey across the entire species range using an occupancy-based analytical approach to (1) establish the first range-wide baseline of occurrence, (2) investigate how environmental and anthropogenic factors influence occurrence, (3) identify priority conservation subpopulations, and (4) test the efficacy of the sampling and analytical protocol for temporal monitoring of M. nigra using occupancy as the state variable. From 9, 753 camera-trap days, M. nigra was detected on 473 days at 77 of the 111 camera locations. Species occupancy was 0.66 and highest inside protected areas and closed canopy forest. We identified eight distinct subpopulations, based on distribution and forest fragment size. To inform future monitoring, we used a power analysis to determine if our effort would allow us to detect inter-annual occupancy declines of 10%, and found that 90 camera locations surveyed for 3 months (8, 100 camera days) across three consecutive seasons is the effort required to detect such change with 80% certainty. Our study underscores the importance of well-managed protected areas and intact forests for the long-term survival of the crested black macaque, and tests the effectiveness of camera traps to monitor primates at the landscape scale.